Interruption in visual search: a systematic review - Cambronero-Delgadillo, Alejandro J.; Nachtnebel, Sarah Jasmin; Körner, Christof; Gilchrist, Iain D.; Höfler, Margit (Frontiers in Psychology, 2024)
Visual search, the process of trying to find a target presented amongst distractors, is a much-studied cognitive task. Less well-studied is the condition in which the search task is interrupted before the target is found. The consequences of such interruptions in visual search have been investigated across various disciplines, which has resulted in diverse and at times contradictory findings. The aim of this systematic review is to provide a more cohesive understanding of the effects of interruptions in visual search. For this purpose, we identified 28 studies that met our inclusion criteria. To facilitate a more organized and comprehensive analysis, we grouped the studies based on three dimensions: the search environment, the interruption aftermath, and the type of the interrupting event. While interruptions in visual search are variable and manifest differently across studies, our review provides a foundational scheme for a more cohesive understanding of the subject. This categorization serves as a starting point for exploring potential future directions, which we delineate in our conclusions.